The Effect of Using Storytelling on Destination Image Is Influenced By Experience - Berto, Agustinus Rusdianto; Putranto, Teguh Dwi; Wahyu, Anabel Yevina Mulyadi; Kurniawan, Bondan Kartiko (UPT Publikasi Ilmiah UNISBA, 2023)
There are still debris of anxiety due to the fatality of the Covid-19 Pandemic which has affected the effect of the tourist experience on the image of the destination of Bali (destination image). This study aims to evaluate the effectiveness of story-telling content on the image of a Bali destination which is mediated by tourist experience or travel experiences in these promotional videos. For this reason, this study tested the theoretical hypothesis of the Elaboration Likelihood Model (ELM) based on the causality relationship between the peripheral route (story-telling variable) and the central route (tourist experience variable) to audience attitudes (destination image variable). In order to achieve this explanatory goal, the researcher uses an experimental method on tourists who have never visited or have visited Bali. The collected data is then tested statistically using path analysis to find the most appropriate causality route model. The results of this study indicate that storytelling does not completely affect the image of the destination but is also influenced by elements of the tourist experience.